Reversible pH‐Responsive Coacervate Formation in Lipid Vesicles Activates Dormant Enzymatic Reactions. Issue 15 (26th February 2020) - Love, Celina; Steinkühler, Jan; Gonzales, David T.; Yandrapalli, Naresh; Robinson, Tom; Dimova, Rumiana; Tang, T.‐Y. Dora
Abstract: In situ, reversible coacervate formation within lipid vesicles represents a key step in the development of responsive synthetic cellular models. Herein, we exploit the pH responsiveness of a polycation above and below its pKa, to drive liquid–liquid phase separation, to form single coacervate droplets within lipid vesicles. The process is completely reversible as coacervate droplets can be disassembled by increasing the pH above the pKa . We further show that pH‐triggered coacervation in the presence of low concentrations of enzymes activates dormant enzyme reactions by increasing the local concentration within the coacervate droplets and changing the local environment around the enzyme. In conclusion, this work establishes a tunable, pH responsive, enzymatically active multi‐compartment synthetic cell. The system is readily transferred into microfluidics, making it a robust model for addressing general questions in biology, such as the role of phase separation and its effect on enzymatic reactions using a bottom‐up synthetic biology approach. Abstract : The pH responsiveness of a polycation above and below its pKa is used to drive liquid–liquid phase separation to form coacervate droplets within lipid vesicles. This is reversible as the coacervate droplets can be disassembled by increasing the pH above the pKa . pH‐triggered coacervation in the presence of low concentrations of enzymes activates dormant reactions as the local enzyme and substrate concentrations are increased in the coacervate droplets which concomitantly changes the local environment of enzymes and reactants.